2015
DOI: 10.18632/oncotarget.3605
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor as a novel molecular target for aggressive papillary tumors in the middle ear and temporal bone

Abstract: Adenomatous tumors in the middle ear and temporal bone are rare but highly morbid because they are difficult to detect prior to the development of audiovestibular dysfunction. Complete resection is often disfiguring and difficult because of location and the late stage at diagnosis, so identification of molecular targets and effective therapies is needed. Here, we describe a new mouse model of aggressive papillary ear tumor that was serendipitously discovered during the generation of a mouse model for mutant EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Pleomorphism is limited, with luminal secretions sometimes noted [36]. In spite of the uncertainty about the exact point of origin, this tumor is more aggressive than either middle ear adenoma or endolymphatic sac tumor, and may respond to targeted molecular therapy [29,37].…”
Section: Aggressive Papillary Tumourmentioning
confidence: 99%
“…Pleomorphism is limited, with luminal secretions sometimes noted [36]. In spite of the uncertainty about the exact point of origin, this tumor is more aggressive than either middle ear adenoma or endolymphatic sac tumor, and may respond to targeted molecular therapy [29,37].…”
Section: Aggressive Papillary Tumourmentioning
confidence: 99%
“…No mutations were detected in KRAS , AKT1 , or EGFR , which are often mutated, respectively, in pancreatic IPMN 14,15 and oncocytic and inverted sinonasal papillomas, 16 salivary gland IPMN, 17 and papillary lesions of the ear in a murine model 18 . Also, no HRAS mutations were found 9 …”
Section: Resultsmentioning
confidence: 96%
“…[9] Histopathologically, the structure of the tumor resembles a renal cell carcinoma, thyroid carcinoma, and papillary variant of choroid plexus tumor. [10] In 1989, Heffner [4] described the similarity between the histopathology of papillary tumors of the middle ear and endolymphatic sac tumors and co-incidence of VHL syndrome, and indicated that aggressive papillary tumors are originally adenocarcinomas of endolymphatic sac epithelium. In 1995, Pollak et al [11] reported that the endolymphatic sac was not involved and originated from the pneumatic cell mucosa around jugular bulbus.…”
Section: Discussionmentioning
confidence: 99%